JPE Turnaround Times, Previous Two Years (Journal of Political Economy, 2021)
Previous articleNext article FreeJPE Turnaround Times, Previous Two YearsFull TextPDF Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJPE Turnaround Times, Previous Two Years Outcome of 1st Round DecisionsMean Days to DecisionMedian Days to DecisionDecision Later than Six Months after Submission (as percentage of decisions within decision type)Desk Rejection53%970%Reject with Reviews39%12010514%Revise8%18615945%Average time from original submission to acceptance (omitting time with author in revision) = 466 days View Table Image Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 129, Number 7July 2021 Article DOIhttps://doi.org/10.1086/715584 Views: 916 © 2021 by The University of Chicago. All rights reserved. Crossref reports no articles citing this article.